GEOCHEMICAL CHARACTERIZATION OF SHALES FROM THE BELAGA FORMATION, CENTRAL SARAWAK, MALAYSIA - MAISIE, MAAME ADWOA (2020)
The Belaga Formation is a thick clastic sequence of turbidites and debrites deposited in a one of the world’s largest submarine fan model. Despite the volumes of research conducted on the Belaga Formation, and the popular hydrocarbon generation potential affiliated to submarine fans deposited by turbidity currents globally, there has been no systematic study on the source rock potential of the shales. Previous studies focused on regional geology, paleontology, petrology and sedimentology with numerous invalidated claims made on the provenance. Compiled information on relevant tectonic assertions follow geological procedures with no geochemical validations yet.